Fracture Resistance Assessment of Wide Canalled, Radicularly Obturated Teeth Using Modified Fiber Post Systems With & Without Accessories - Ben Ramadan, Aisha; Elkawash, Hend; Abdalla, Moamen (Libyan Journal of Dentistry, 2020)
Background: Wide canalled endodontically treated teeth present a common clinical challenging problem. Objectives: Aiming to perform fracture resistance assessment of modified fiber post systems with differ- ent forms of customization as an effective treatment modality in the wide canalled teeth. Methods: Freshly extracted twenty-eight maxillary central incisors were collected. Teeth were resected coronally above the cervix, radiculary prepared and obturated. Resected teeth were randomly grouped according to fiber post modification as (Group I) Custom-made post by fiber impregnated strands (CMF). (Group II) Customized fiber posts by composite (CF). (Group III) Prefabricated fiber post with accessory posts (PA). (Group IV) Prefabricated fiber posts without accessory posts (PNA). All samples were mounted on universal testing machine for fracture resistance measurements. All measurements were recorded and statistically analyzed One-way ANOVA testing along with pair-wise Tukey’s post-hoc testing. Results: The modified fiber post system studied has been significantly varied in the results, declaring that Prefabricated fiber with Accessory (PA) group recorded the highest mean ± SD value of fracture resistance (373.02±27.967 N) followed by Custom made resin impregnated fiber (CMF) group which recorded mean ± SD value of (357.48±28.748 N) then Prefabricated fiber post without Accessory group with mean ± SD value of (264.41±25.175 N) meanwhile the lowest mean ± SD value was recorded with Customized fiber post with composite (CF) group (246.4±20.948 N). Conclusion: Accordingly with the results elaborated it can be speculated that utilization of accessory posts will provide a safe and rigid alternative in those cases by decreasing the interpenetrating thickness of ce- menting resin on mesial and distal sides of the master post cemented and creating a better root canal-post adaptation.